Phase II Study of Lorlatinib in Patients With Anaplastic Lymphoma Kinase–Positive Lung Cancer and CNS-Specific Relapse. (18th May 2022) - Dagogo-Jack, Ibiayi; Oxnard, Geoffrey R.; Evangelist, Makenzi; Digumarthy, Subba R.; Lin, Jessica J.; Gainor, Justin F.; Murphy, John F.; Rabin, Michael S.; Heist, Rebecca S.; Muzikansky, Alona; Shaw, Alice T.
Abstract : PURPOSE: The CNS is a recurrent site of progression in anaplastic lymphoma kinase (ALK)–rearranged (ALK+) lung cancer. Lorlatinib is a third-generation ALK inhibitor developed to penetrate the CNS and overcome ALK resistance mutations. We conducted a phase II study to evaluate the intracranial activity of lorlatinib in patients with CNS-only progression on second-generation ALK inhibitors. METHODS: Patients with ALK+ lung cancer who had intracranial progression on ≥ 1 ALK inhibitor without measurable extracranial disease received lorlatinib 100 mg once daily. The primary end point was intracranial disease control rate at 12 weeks per modified RECIST v1.1. Secondary end points included intracranial progression-free survival, intracranial objective response rate, and safety/tolerability. RESULTS: Twenty-three patients were enrolled between November 2016 and January 2019. Fifteen (65%) patients had irradiated CNS metastases, with a median of 20.2 months between radiation and lorlatinib. Control of intracranial disease was observed in 21 (95%) evaluable patients at 12 weeks. The intracranial objective response rate was 59% with six complete and seven partial responses. The median intracranial progression-free survival was 24.6 months (95% CI, 20.2 to not reached). With a median follow-up of 16.8 months, nine patients developed disease progression, including four patients with CNS progression. The most common treatment-related adverse events were hypercholesterolemia (96%), hypertriglyceridemia (87%), edema (65%), cognitive effects (52%), and mood effects (43%). Three patients discontinued treatment because of toxicity, including two patients with fatal respiratory events. CONCLUSION: Lorlatinib induced durable intracranial disease control in patients with CNS-only relapse on second-generation ALK inhibitors, suggesting that tumors with CNS-limited progression on brain-penetrant ALK tyrosine kinase inhibitors remain ALK-dependent. Abstract : Lorlatinib demonstrated robust CNS activity in a study of patients with CNS-only relapse on ALK TKIs.